ENHANCING PQRST LEARNING MODEL FOR VOCATIONAL HIGH SCHOOL STUDENTS’ LEARNING READING - Haryono, Purwo; Widayanti, Sukasih Ratna; Yulianti, Ferryka (WIDYA DIDAKTIKA - Jurnal Ilmiah Kependidikan, 2024)
This study aimed at finding how the PQRST learning model is applied in teaching and learning reading for students of vocational high school. The design of the research was descriptive qualitative. The data were activities of teaching and learning reading which were collected by using observation, interview, and documentation techniques. The data were, then, analyzed descriptively. The result showed that the students’ achievement was 64.52 before applying PQRST learning model and 77.09 after using it. The number of students who passed minimum completeness criteria increased from 12 to 20 out of 21 students. It is, then, recommended that English teachers use PQRST learning model to improve students’ reading comprehension.